(untitled) (Mustansiria Dental Journal, 2024)
The S2-complex drug is a chemical preparation of a low molecular weight synthetic organometalic complex, and it has experimented in many researches to prove it’s activity in the treatment of the cancerous tumors, without any side effects. This drug is a potent immunomodulat or that stimulates both, the humoral a.nd cell mediated ,immune responses To examine the effect of S2—complex administered locally and was designed to test the potential effectiveness of S2-complex in the management of periodontal disease .associated bone loss by radiographic evaluation Thirty six pairs of similarly involved periodontal pockets in (20) patients aged between (30-50) years old with pocket depth more than 6 mm were selected. Split mouth ,randomized study was carried out. Scaling and root planing was carried out in both sides in test side received S2- complex for five days in a daily dose of O.l mm/kg injected deeply until reaching the bone of affected site, while the control side was received distal water for 5 days in a daily dose of 0.l mm/kg injected in the same way as that for test side. S2 complex was infiltrated locally through the gingival tissue of the effected site .deeply until reach the defect bone using disposable insulin syringes Clinical attachment level of gingiva were recorded at baseline and repeated once every 2 weeks. Periapical radiographs were taken for both test and control sides at baseline and at the termination of the treatment after 2 months. A long the time of study ,the patients put on a program of motivation to keep a good stander of oral hygiene Clinical and radiographical parameters in general showed improvement with both test .and control groups, with a statical significant difference between them Radiographical evaluation showed high differences in hight and density of bone for both groups, and effect to S2-complex was on sites of anterior and molar areas according